First cytogenetic information for Drymoreomys albimaculatus (Rodentia, Cricetidae), a recently described genus from Brazilian Atlantic forest - Suárez-Villota, Elkin Y.; Di-Nizo, Camilla B.; Neves, Carolina L. [UNESP]; Silva, Maria José de Jesus (Pensoft Publishers, 2013)
The recently described taxon Drymoreomys albimaculatus is endemic to the Brazilian Atlantic Forest and its biology and genetics are still poorly known. Herein, we present, for the first time, the karyotype of the species using classical and molecular cytogenetics, which showed 2n=62, FN=62, and interstitial telomeric signals at the sex chromosomes. Nuclear and mitochondrial DNA sequences from the two karyotyped individuals verify the taxonomic identity as the recently described D. albimaculatus and confirm the relationship of the species with other Oryzomyini. Additionally, external morphological information is provided. © Elkin Y. Suárez-Villota et al.
Keywords: CBG banding; Cyt b; FISH; GTG banding; IRBP; Karyotype; Oryzomyini